Incidental detection of Cladosporium in cytology - Tummidi Santosh; Indranil Chakrabarti; Aparna Palit; Sonakshi Srivastava (BMC, 2024)
Abstract Background Fungal infection incidental detection is a common encounter in cytopathology practices. Detection of the fungal organisms and awareness of the morphological features are challenges for the cytopathologist. Case presentation We report a case of incidental detection of a fungal organism in a 67-year-old male patient with complaints of bilateral elbow joint swellings. Cytology was done and showed a fungal organism (Cladosporium sps.). Conclusion Fine needle aspiration cytology (FNAC) along with Rapid on-site evaluation (ROSE) is a rapid, minimally invasive technique used for the diagnosis and detection of various fungi / parasites leading to early and definitive treatment.